Asphalt Mixing Performance Evaluation at Province Road Junction Sta 1+700 - 2+300 - Nanang Tawaf; Ady Purnama (LPPM of NAROTAMA UNIVERSITY, 2023)
Asphalt mixture is a very important component that needs to be taken into account in flexible pavement construction to achieve the durability of a highway construction. In order to achieve the durability of road construction, it is necessary to control the quality of the mixture used to determine the quality of the mixture used in road construction. Evaluation of the mixture is carried out in the laboratory to check asphalt content, aggregate gradation and field density which must meet the required tolerances for the working mixture (JMF). Evaluation of the asphalt mixture can be done by the extraction method. The extraction method used in this study is the centrifugal extraction method. With this extraction method, the composition of a mixture can be known so that it can be compared with the mixture required in the Job Mix Formula (JMF). In conclusion, there is a decrease in the extracted asphalt content with the planned asphalt content, that is, with an average asphalt content value of extraction results of 6. 58% while the planned asphalt content value is 7.10% with the required tolerance of ±0.3%. In addition to the value of asphalt content, the field density also decreased from that which was planned in the work mix. It is known that the density value in the work mixture is 2,250 g/mm3 while the average field density value is 2,095g/mm3 so that the Job Standard Density (JSD) value is 93.108% and this value is below the tolerance limit. Then the aggregate gradation of the semi-gap HRS WC mixture at the Intersection section of the Lito province on average underwent a gradation change, namely a decrease in the percentage of passing on each sieve.